The influence of mat Pilates training adherence on strength and flexibility parameters in breast cancer survivors undergoing hormone therapy - Bertoli, Josefina [UNESP]; Bezerra, Ewertton de Souza; Santos, Sueyla Ferreira da Silva dos; Gobbo, Luis Alberto [UNESP]; Freitas, Ismael Forte [UNESP] (Korean Society of Exercise Rehabilitation, 2022)
The aim of this study was to evaluate the influence of adherence to mat Pilates training on lower and upper body strength and flexibility in breast cancer survivors. Breast cancer survivors (≥40 years) with cancer stages 0–III undergoing hormone therapy participated in this study. For this secondary investigation only the intervention group was analyzed, divided into low and high training adherence. Participants performed a 60-min session of mat Pilates, 3 times/wk, for 24 weeks. Concentric, ec-centric, and isometric hip flexor-extensor muscle peak torque, and iso-metric maximal strength parameters of the shoulder abductors, trunk extensors, and handgrip were assessed. Physical activity level was an-alyzed as a control variable. The results showed that high training ad-herence improved (P<0.05) left shoulder abductor strength parameters and lower and upper body flexibility compared to baseline. The low training adherence group improved (P<0.05) trunk extensors, right and left shoulder abductor strength parameters, handgrip strength, and ex-tensor-flexor peak torque compared to baseline. There were no differ-ences (P>0.05) between high and low adherence for physical activity level before and after the intervention. Therefore, it appears that higher training adherence most influences some strength parameters and flexibility, while fewer sessions enable the achievement of significant results for shoulder abductor and hip extensor-flexor muscle strength parameters.
Keywords: Breast neoplasms; Exercise movement techniques; Exercise therapy; Muscle strength; Physical fitness; Range of motion